Nobiltà e monasteri femminili nel Trecento romano: il caso dei conventi delle clarisse di San Silvestro in Capite e di San Lorenzo in Panisperna - Rehberg, Andreas (Reti Medievali Rivista, 2018)
Medieval female monastic life in Rome has as yet not become subject of extended studies. The present contribution is analysing the social and cultural backgrounds of two Roman convents of the order of St. Clare, namely the convents of San Silvestro in Capite and of San Lorenzo in Panisperna. Their historical backgrounds are similar as both convents emerged in the orbit of the Colonna family. These origins are raising many questions about the complex relations during the XIVth century between the powerful families of the Roman barons and the female convents in the city of Rome. The analysis of the precarious archival documentation is concentrated on the circumstances of these two foundations, both for their social implications (reconstructing the networks of relatives and families allies of the Colonna) and for the religious and spiritual aspects.